2003
DOI: 10.1039/b310860k
|View full text |Cite
|
Sign up to set email alerts
|

Novel alignment technique for LCD-biosensorsElectronic supplementary information (ESI) available: alignment layer formation and structure, FT-IR spectra and polarising microscopic images. See http://www.rsc.org/suppdata/cc/b3/b310860k/

Abstract: The directional drying of a low-salt Tris-EDTA (TE)-buffer to give an alignment layer offers a simple, one-step, non-contact procedure for the construction of parallel liquid crystal displays (LCDs), which can be used to amplify the presence of DNA to scales visible to the naked eye, opening up possibilities for easy detection of bio recognition events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Other applications exploit liquid crystals' sensitivity to surface interactions, for example, the detection and amplification of the presence of DNA to the visible eye and as novel alignment techniques for biosensors [64]. • Chiral Solvents -because liquid crystal phases are anisotropic, it is possible to use them as solvent templates in which polymerizations can take place to form anisotropic polymer structures.…”
Section: Applications Of Chiral Nematic Phasesmentioning
confidence: 99%
“…Other applications exploit liquid crystals' sensitivity to surface interactions, for example, the detection and amplification of the presence of DNA to the visible eye and as novel alignment techniques for biosensors [64]. • Chiral Solvents -because liquid crystal phases are anisotropic, it is possible to use them as solvent templates in which polymerizations can take place to form anisotropic polymer structures.…”
Section: Applications Of Chiral Nematic Phasesmentioning
confidence: 99%
“…There are two limitations. First, the proper alignment of LC at the substrates with receptors is challenging [5], as the receptors should function simultaneously as the antibody-specific sites and as aligning agents for the LC. Second, the LCs capable of anchoring transitions are usually of the thermotropic (solvent-free) oil-like type [8], practically immiscible with water which is the typical carrier of many biological species.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in using the nematic liquid crystals (NLCs) in biological sensors as the medium that amplifies the molecular-and submicron-scale reactions such as ligand-receptor binding to the macro-scale accessible for optical detection [1][2][3][4][5][6][7]. Abbott et al proposed a technique based on anchoring transition at the nematic surface [1].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] This qualifies liquid crystals as molecular magnifying glasses, bringing (bio)reactions which occur on nanoscales into the realm of the naked eye, without the need for additional processing. [1][2][3][4][5][6][7][8][9][10][11] Recently, we described a procedure for the preparation of selfassembled alignment layers for liquid crystal alignment purposes, which makes use of parallel nanometre-sized grooves that are present on commonly used indium-tin-oxide (ITO) surfaces. 12 The size of these grooves is amplified over several orders of magnitude by the anisotropic grafting of oligosiloxanes, which spontaneously form in situ, onto the ITO surface, resulting in liquid crystal alignment over millimetre-sized areas.…”
mentioning
confidence: 99%
“…After 1 h, the plate was removed from the solution, washed with acetonitrile and baked at 120 uC for 10 min to complete the covalent bonding of the siloxanes to the surface. When these surfaces were used in liquid crystal cells, 11 I polarising microscopy showed that the siloxane layers were capable of inducing uniform alignment of the common nematogen n-pentyl-4,49-cyanobiphenyl, 5CB (Fig. 1a).…”
mentioning
confidence: 99%